Hyperbranched Polyamines: Tunable Catalysts for the Henry Reaction - Ganesan, Subramaniapillai Selva; Ganesan, Asaithampi; Kothandapani, Jagatheeswaran (Synlett, 2014)
Hyperbranched polyethylenimine derivatives were successfully employed as catalyst in the Henry reaction. The nitroalcohol products were obtained in excellent yields within short reaction times. A one-pot synthesis of β-nitrostyrenes was developed by using ZnCl2 along with hyperbranched polyethylenimine derivatives.
Keywords: Henry reaction; diastereoselectivity; polyamine; homogeneous catalysis; β-nitrostyrene